Pengaruh Kompetensi, Independensi Dan Komitmen Organisasi Terhadap Kinerja Auditor Pada Bpkp Perwakilan Diy - Endah Wulandari; Heru Kurnianto Tjahjono (Universitas Muhammadiyah Yogyakarta, 2011)
Nowadays, a new paradigm emerges which points out the role of an auditor is no longer considered as watch dog to cause fear among auditees. Here, the auditor is taking the role of consultant and catalyst. In term of competence, an auditor can also propose the role of witness or expert witness on a trial. Audit report can be used as a dossier's material in a criminal proceeding by police, district attorney, or court. It proves that audit report is legal evidence that supports a case's completion. At this point, audit report should reflect its auditor's competence in which his or her performance will be tested on the court. Auditor, as a profession, is like two sides of a coin. In one sense, auditor is expected to create good public governance. On the other hand, there are risks to deal with, such as, auditee’s pressure, weaponry threat, and psychological threat. There is also ‘less harmful’ threat namely bribery in form of table money or transportation fee. However, these types of threat should not influence the auditor's independence in making decision. In addition, there is still so called political influence that may affect the auditor's independence. This research aims to analyze the effect of organizational competence, independence, and commitment to auditor's performance. Sample of the research was 87 respondents from Finance and Development Supervisory Agency (BPKP) of Yogyakarta Special Province. In answering the research's hypothesis, the researcher used multiple linear regression analysis, preceded by hypotheses testing. The result shows that competence and independence have significant roles in auditor's performance. Additionally, affective and normative commitments give influence to auditor's performance. However, continuance commitment does not influence the auditor's performance.